2013
DOI: 10.1111/ijsw.12059
|View full text |Cite
|
Sign up to set email alerts
|

Labor force participation among Asian immigrant women: Findings from the 2007 American Community Survey

Abstract: Using a nationally representative sample of Asian immigrant women in the USA (N = 33,032), we examined ethnic variations in labor force participation and different predictors of labor force participation among six Asian ethnic subgroups, including Chinese, Filipino, Asian Indian, Vietnamese, Korean, and Japanese. Our findings indicated that having a higher level of education, fewer children under age 5, US citizenship, a longer length of residence in the USA, and a better English proficiency were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Salway (2007) reports that cultural scripts in Pakistan constrain the market employment of married women, and the presence of extended family members may reinforce this code of conduct. However, Pakistani women also may face legal constraints on employment associated with their visas (Lee, Zhou, & Kim, 2014). Unfortunately, information about respondents' visa status as well as the type of visa is not available in ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Salway (2007) reports that cultural scripts in Pakistan constrain the market employment of married women, and the presence of extended family members may reinforce this code of conduct. However, Pakistani women also may face legal constraints on employment associated with their visas (Lee, Zhou, & Kim, 2014). Unfortunately, information about respondents' visa status as well as the type of visa is not available in ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prior studies have shown that there is variation in immigrant women’s experiences in the labor market by race/ethnicity and country of origin (Lee, Zhou, and Kim 2014; Shin and Liang 2014). Differences in migration experiences lead to diverging in labor-market outcomes and labor force participation across multiple Asian ethnic groups.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Especially Asian American women who immigrated after high school are highly disadvantaged, even if they hold the highest degree from a United States institution. Regarding language, previous research found that immigrants who are proficient in English have higher rates of socioeconomic success, including higher earnings (Borjas 1994;Chiswick and Miller 2012;Grenier 1984;Lee, Zhou and Kim 2013;McManus et al 1983). Grenier (1984) showed that immigrants who could not speak English faced a 17% wage penalty.…”
Section: Predictors Of Socioeconomic Successmentioning
confidence: 99%